Translation of remote ischaemic preconditioning into clinical practice. - Kharbanda, R; Nielsen, T; Redington, A (2009)
Reduction of the burden of ischaemia-reperfusion injury is the aim of most treatments for cardiovascular and cerebrovascular disease. Although many strategies have proven benefit in the experimental arena, few have translated to clinical practice. Scientific and practical reasons might explain this finding, but the unpredictability of acute ischaemic syndromes is one of the biggest obstacles to timely application of novel treatments. Remote ischaemic preconditioning-which is a powerful innate mechanism of multiorgan protection that can be induced by transient occlusion of blood flow to a limb with a blood-pressure cuff-could be close to becoming a clinical technique. Several proof-of-principle and clinical trials have been reported, suggesting that the technique has remarkable promise. We examine the history, development, and present state of remote preconditioning in cardiovascular disease.